Envelhecimento dinâmico em aço Dual Phase de 600 MPa de limite de resistência - Rhelman Rossano Urzedo Queiroz (2013)
The susceptibility to dynamic strain aging of a dual phase steel was evaluated by the variation of mechanical properties in tension with the temperature and the strain rate. The tensile tests were performed at temperatures varying between 25 ºC a 600 ºC and at strain rates ranging from 5 x 10-6 s-1 to 10-1 s-1. The studied steel presented typical manifestations related to dynamic strain aging: serrated flow (the Portevin Le Chatelier effect) for certain combinations of temperature and strain rates; the presence of a plateau in the variation of yield stress with temperature; a maximum in the curves of tensile strength, flow stress, and work hardening exponent as a function of temperature; and a minimum in the variation of total elongation with temperature. The determined apparent activation energy values, associated with the beginning of the Portevin Le Chatelier effect and the maximum in the variation of flow stress with temperature, were 87 kJ/mol and 168 kJ/mol, respectively. These values suggest that the mechanism responsible for dynamic strain aging in the dual phase steel is the locking of dislocations by carbon atoms in ferrite. Both, the phenomenological and the kinetic aspects, did not indicate the contribution of clustering and/or transition carbide precipittion in ferrite or carbide precipitationin in martensite, as occurs in strain aging. Undeformed and deformed steel samples at temperatures of 25 ºC, 200 ºC, 300 ºC, 350ºC e 400 ºC and strain rate of 10-3 s-1 were prepared in a form of thin foil and examined byelectron transmission microscopy in order to analyze changes in dislocations substructure at temperatures range in which the dynamic aging occurs. Significant changes were observed in the dislocations pattern that evolved from a uniform distribution, in deformed material at room temperature, to a distribution in form of parallel walls at 200 ºC and300 ºC, culminating in a complex substructure with high dislocation density at 350 ºC. At 400 ºC, it is no longer possible to observe the same dislocations density as at 350 ºC and the distribution pattern differs to the one presented at 200 ºC and 300 ºC, i.e., there is no more dislocations cluster formation in defined regions of the sample. The obtained images did not indicate any formation of clusters and/or transition carbides or carbide precipitation in martensite during the straining at temperatures in which were observed the dynamic strain aging effects.